Biosurveillance for an invasive pest of maize, Prostephanus truncatus, across North America and in Greece - Quellhorst, Hannah E.; Sakka, Maria K.; Odjo, Sylvanus; Ludwick, Dalton; Bingham, Georgina V.; Roeder, Karl A.; Hesler, Louis S.; Hanley, Raina M.; Zhu, Junwei J.; Wilkins, Rachel V.; Ponce, Marco A.; Athanassiou, Christos G.; et al. (Wiley, 2025)
Biosecurity is an increasingly important aspect of management of commodities in a globalised economy. The larger grain borer, Prostephanus truncatus, is a known biosecurity threat to the United States and has been classified as a species-of-concern. Under climate change, P. truncatus is expected to expand its range into the United States from Mexico. In this study, we performed a 2-year latitudinal biosurveillance programme for P. truncatus, related bostrichids and Sitophilus spp. as key species in and around maize and wheat production at 10-15 sites from 20 degrees to 47 degrees latitude in North America and Greece to evaluate how habitat, latitude and season affected spatiotemporal dynamics of these insects. Two types of traps, a 4-funnel Lindgren and pitfall traps, were deployed at each site, baited with each species' pheromones. In total, we captured 2528 insects in 2021 and 29,080 insects in 2022. P. truncatus was only documented in Mexico but in high abundance in both years. Interestingly, even though P. truncatus is a good flier, the funnel trap was equally effective as the pitfall trap in monitoring P. truncatus. Conspecifics were found most often in natural and row crop habitats in both years compared to food facilities. Captures of P. punctatus in 2022 most often occurred in natural habitats, but they were still present at row crops and near food facilities. By contrast, Sitophilus spp. were most associated with food facilities. Overall, this study helps inform current risk from P. truncatus and fundamental patterns of spatiotemporal distribution for several related key stored product insects.